New species of Andropromachus (Phasmatodea: Lonchodidae: Necrosciinae: Necrosciini) from Yunnan Province, China - ChongXin Xie; Jun Cai; YuHan Qian (Biodiversity Data Journal, 2022)
The genus Andropromachus (Lonchodidae: Necrosciinae: Necrosciini) is a small genus of stick insects including four species with a distribution in northern Vietnam and south-western China.A new species of stick insects Andropromachus gulinqingensis sp. n. is described from Yunnan Province of China. Diagnostic characters of the new species are illustrated and an identification key to male and female Andropromachus is provided along with a checklist for all described species.